Accuracy of Measles Immunization Records and Reporting in Maternal and Child Health Card and Cohort Book - Rekha Finazis (Jurnal Berkala Epidemiologi, 2014)
Communicable diseases such as diseases that can be prevented by immunization remain a problem in Indonesia, one of which is measles. The government has sought to prevent measles immunization in infants aged 9 months, but the measles case still found in Indonesia, so it’s necessary to evaluate the success of programs related to measles immunization. This study was conducted to determine the problems that occur in terms of recording and reporting of data related to measles immunization in particular measles immunization data quality. The population was 5 integrated health care posts (Posyandu) with the highest number of children under five in the region of the new Public health center (PHC) of Gunung Anyar Surabaya. The number of respondents is as much as 50 respondents with details of each in integrated health care post will take 10 respondents. The sample selection is done through a rapid survey method. The variables studied were the quality of immunization data on maternal and child health cards (KIA/KMS) or other records compared with immunization data on a cohort book. Other variables are the quality of data on infants in integrated health care post register book by book cohort. The results showed that the percentage of the suitability of the data of measles in the community with book five cohort remains low in the integrated health care post. Meanwhile, the percentage of suitability data on the register books with babies in integrated health care post cohort book is also fairly low. This suggests that the quality of data recorded in measles immunization is relatively low.